Oral myiasis in children - M H Raghunath Reddy; Nagarajappa Das; M R Vivekananda (Wolters Kluwer Medknow Publications, 2012)
Oral myiasis is a rare condition in humans and is associated with poor oral hygiene, severe halitosis, mouth breathing during sleep, mental handicap, cerebral palsy, epilepsy, anterior open bite, incompetent lips, and other conditions. In this report, a 14 year-old boy who had an orofacial trauma in the maxillary dentoalveolar region,which was neglected, has been described. There was a deep lacerated wound on the upper vestibule which was infected and maggots were found on the same wound. The clinical features, management, treatment are discussed and relevant literature is reviewed.